Odisha vision 2036 and 2047 : Viksit Odisha for Viksit Bharat - Planning and Convergence Department, Govt. of Odisha (Bhubaneshwar Planning and Convergence Department, Govt. of Odisha, 2025)
Odisha Vision 2036 & 2047 is a comprehensive plan to transform Odisha into a developed state by 2036 and a USD 1.5 trillion economy by 2047, as part of the broader "Viksit Odisha for Viksit Bharat" (Developed Odisha for a Developed India) initiative. This vision is built on six pillars: rural empowerment, people-first development, legacy and pride, prosperity for all, technology leadership, and citizen-centric .governance. It also includes a "36-for-36" agenda, a set of 36 high-impact initiatives for transformative change by 2036
Keywords: Vision Document; Viksit Odisha